MHRA guidance on assessing renal function. Issue 2 (10th December 2019) - Unknown
Abstract : Every month, DTB scans sources of information on treatments, disease management and other healthcare topics for key items to bring to our readers' attention and help them keep up to date. To do this, we produce succinct, contextualised summaries of the information concerned.